The Arab Republic of Egypt : For Better or For Worse, Air Pollution in Greater Cairo - World Bank (Washington, DC, 2013)
This sector note presents the results of the World Bank-led study on the development of a strategy of the government of the Arab Republic of Egypt to respond to air quality problems in Greater Cairo. The Greater Cairo Metropolitan Area (GCMA) is the largest urban and industrial center in Egypt, which, in 2009, was ranked eighth among the world's top urban agglomerations. Twenty million people live and work in Greater Cairo, which is surrounded by major heavy industries to the north and the south, including large, as well as small and medium enterprises. As in many megacities in the world, air pollution has been a chronic problem in Greater Cairo. The persistent air quality problem represents a serious hurdle to the competitiveness that is a key to the socioeconomic development of Greater Cairo and therefore the nation. An action plan has prepared for the implementation of the main sectorial policies. This action plan will have to be developed and changed where required because it can only be implemented within a coherent framework of environmental, energy, and economic policies that need to be defined and adopted by the government. Therefore, the action plan, as presented in this report, should be considered as a basis for ongoing discussions with the government. These discussions must, in any case, be continued to support the implementation of the work that has been initiated through this report. The action plan also identifies the entities that should be involved in or responsible for implementing and monitoring specific activities.